Risk Factors and Imaging Characteristics of Childhood Stroke in China. (March 2015) - Deng, Yaxian; Wang, Yilong; Yang, Weili; Yu, Yazhen; Xu, Juanyu; Wang, Yongjun; Gao, Baoqin
There are scarce reports of childhood stroke from China. Our objective was to describe the clinical spectrum, risk factors, and imaging characteristics of childhood stroke in China. Using a hospital discharge database, children with stroke who were first admitted from 2002 to 2011 were retrospectively enrolled. We identified 478 first admissions with childhood stroke, including 229 cases of ischemic stroke and 249 hemorrhagic stroke. Boys accounted for more than 60% in all stroke types (62.2% for ischemic stroke, intracerebral hemorrhage for 66.2%). The leading cause was moyamoya for ischemic stroke and arteriovenous malformations for intracerebral hemorrhage. Hemiplegia and headache were the most common presenting features. Internal carotid artery and middle cerebral artery were the most involved arteries according to imaging examination in the ischemic stroke. A total of 8 patients died of intracerebral hemorrhage. The prevalence of hemorrhagic stroke was more than that of ischemic stroke. As Western countries, arteriopathy was the most common cause of childhood stroke.